2018
DOI: 10.1007/s00330-018-5725-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative prediction of cavernous sinus invasion by pituitary adenomas using a radiomics method based on magnetic resonance images

Abstract: Objectives To predict cavernous sinus (CS) invasion by pituitary adenomas (PAs) pre-operatively using a radiomics method based on contrast-enhanced T1 (CE-T1) and T2-weighted magnetic resonance (MR) imaging. Methods A total of 194 patients with Knosp grade two and three PAs (training set: n = 97; test set: n = 97) were enrolled in this retrospective study. From CE-T1 and T2 MR images, 2553 quantitative imaging featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…The tumor size and the Knosp grade were determined using preoperative pituitary contrast-enhanced MRI images ( 20 , 21 ). The cavernous sinus invasion ( 22 ) and the tumor texture ( 2 ) were determined by the surgeon during the operation. The cavernous sinus invasion of tumors was considered to be positive if the tumor extended the cavernous sinus and a cavernous sinus defect was observed ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…The tumor size and the Knosp grade were determined using preoperative pituitary contrast-enhanced MRI images ( 20 , 21 ). The cavernous sinus invasion ( 22 ) and the tumor texture ( 2 ) were determined by the surgeon during the operation. The cavernous sinus invasion of tumors was considered to be positive if the tumor extended the cavernous sinus and a cavernous sinus defect was observed ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, radiomics is playing an increasingly important role: its preoperative prediction of CS invasion based on contrast-enhanced T1 and T2-weighted magnetic resonance (MR) imaging might support clinical decision-making and predict outcomes [127]. Three-dimensional anisotropy contrast (3DAC) MR imaging [128], CE-MRA 3T (contrast-enhanced MR angiography) [129] or CE 3D FIESTA (contrast-enhanced 3D fast-imaging employing steady-state acquisition) [130] might be used to evaluate CS invasion and study the involvement of its cranial nerves.…”
Section: Radiological Technical Advancementsmentioning
confidence: 99%
“…Recent studies have shown several applications of radiomics in meningiomas, such as different diagnoses, prediction of the grade and histological subtype, and prediction recurrence-free survival in meningioma [ 5 , [15] , [16] , [17] ]. Moreover, a recent study showed that radiomics might predict preoperative cavernous sinus invasion by pituitary adenomas [18] . These studies show the value of radiomics in medical imaging, which can also be a potential method for the prediction of brain invasion in meningiomas on MRI.…”
Section: Introductionmentioning
confidence: 99%